Disseminated intravascular coagulation and melanoma: a novel case occurring in metastatic melanoma with BRAF and NRAS mutations and systematic review. Issue 5 (October 2019) - Haggstrom, Lucy; Duong, Tuan Anh; Thomas, Benjamin; Brungs, Daniel; Aghmesheh, Morteza; Parmar, Gurdeep
Abstract : Disseminated intravascular coagulation is a complex and potentially lethal complication of malignancy, in which the fundamental abnormality is excessive activation of the coagulation system. It is a rare complication of melanoma which can be difficult to diagnose in some circumstances, leading to delay in treatment. Herein, we describe the first case of disseminated intravascular coagulation occurring in BRAF and NRAS -mutant metastatic melanoma, and systematically review the literature regarding disseminated intravascular coagulation in melanoma. This review summarizes the reported cases of disseminated intravascular coagulation in melanoma and those secondary to the novel treatment of melanoma, and explores the pathophysiology of disseminated intravascular coagulation in melanoma, highlighting the key role of expression of markers of coagulation and fibrinolysis in disseminated intravascular coagulation, as well as more widely in melanoma. Current limitations in the literature are also identified and discussed, particularly with respect to improving the management of this lethal complication. Disseminated intravascular coagulation is a rare complication of melanoma that typically portends poor prognosis. Abstract : Supplemental Digital Content is available in the text.